Defective XRN3‐mediated transcription termination in Arabidopsis affects the expression of protein‐coding genes. (20th February 2018) - Krzyszton, Michal; Zakrzewska‐Placzek, Monika; Kwasnik, Aleksandra; Dojer, Norbert; Karlowski, Wojciech; Kufel, Joanna
Summary: Arabidopsis thaliana contains two nuclear XRN2/3 5′–3′ exonucleases that are homologs of yeast and human Rat1/Xrn2 proteins involved in the processing and degradation of several classes of nuclear RNAs and in transcription termination of RNA polymerase II. Using strand‐specific short read sequencing we show that knockdown of XRN3 leads to an altered expression of hundreds of genes and the accumulation of uncapped and polyadenylated read‐through transcripts generated by inefficiently terminated Pol II. Our data support the notion that XRN3‐mediated changes in the expression of a subset of genes are caused by upstream read‐through transcription and these effects are enhanced by RNA–mRNA chimeras generated in xrn3 plants. In turn, read‐through transcripts that are antisense to downstream genes may trigger production of siRNA. Our results highlight the importance of XRN3 exoribonuclease in Pol II transcription termination in plants and show that disturbance in this process may significantly alter gene expression. Significance Statement: Polymerase II transcription termination is a critically important step in gene expression that is poorly characterized in plants. We show that defects in this process caused by knockdown of Arabidopsis thaliana 5′–3′ exoribonuclease XRN3 lead to complex disturbances in mRNA levels that are mediated by read‐though transcripts.